Unveiling the Problems of Student Teachers during Practice Teaching in Nueva Ecija, Region III, Philippines - Leila Collantes (Indonesian Research Journal in Education |IRJE|, 2021)
Using purposive sampling, 386 student teachers were profiled and investigated on the problems they met during their deployment to 63 schools under four Teacher Education Institutions in Region III for the conduct of their practice teaching. Data were collected using a two-part survey questionnaire consisting of the student teachers’ profile and problems they met then analysed through descriptive method using frequency, percentage, and rank. The study revealed that the problems encountered by student teachers include cooperating teachers do not hold regular class observations, noisy and talkative students, students’ difficulty in expressing themselves in English, too much assignment given by school administrators and student teaching supervisor, uncooperative fellow student teachers, and lack of time and resources in preparing instructional materials